BUSINESS ECONOMICS - SANKARAN S (CHENNAI MARGHAM PUBLICATIONS, 2024)
"Business Economics" by Dr. S. Sankaran is a foundational textbook widely used in Indian universities that explains core concepts and applications of economics from a business perspective, with a focus on managerial decision-making and real-world problem-solving.
ECONOMICS
ECONOMICS
BBA & MBA
Keywords: BUSINESS; ECONOMICS